Occupational health literacy and work ability: a moderation analysis including interpersonal and organizational factors in healthy organizations - Friedrich, Julian; Rupp, Maylin; Feng, You-Shan; Sudeck, Gorden (Frontiers in Public Health, 2024)
Healthy organizations approach for occupational safety and health should holistically include individual, interpersonal and organizational levels. There is an empirical research gap in considering different levels in organizations for health promotion in the context of maximizing work ability. This study aims to investigate the association of 1) occupational health literacy (individual level), 2) health-oriented leadership (interpersonal level), 3) participation possibilities in health and 4) values of health in companies (both organizational levels) on work ability. Additionally, we examined the potentially moderating role of health-oriented leadership, participation possibilities in health and values of health between occupational health literacy and work ability. Methods Cross-sectional data were obtained from 828 employers and employees in small and medium-sized enterprises. Self-report measures included occupational health literacy, health-oriented leadership, work ability, participation possibilities in health at work and values of health in the company. Occupational health literacy comprises two factors: a knowledge-/skill-based approach to occupational health and a willingness/responsibility for occupational health. Participation possibilities in health is measured regarding participatory opportunities and co-creation of health at work. Values of health in the company capture the importance of health in the workplace and the scope for improving employees’ health. Data were analyzed using latent regression and latent moderation analyses controlling for age, gender and educational level. Results Occupational health literacy (knowledge-/skill-based), health-oriented leadership, participation possibilities in health, and values of health in companies showed positive associations with work ability. Health-oriented leadership on an interpersonal level was found to moderate the positive relationship between the (knowledge-/skill-based) occupational health literacy and work ability. Participation possibilities in health on an organizational level acted as a moderator on the relationship between both occupational health literacy factors and work ability. Discussion Individual, interpersonal and organizational factors play important roles in maintaining work ability in healthy organizations. This study highlights the importance of promoting occupational health literacy among employees and leaders, creating a healthy workplace through health-oriented leadership and providing participatory opportunities for co-creation in health promotion at work. Future research should further explore these factors’ roles in different industries and contexts and how they may be addressed effectively in tailored workplace interventions.